Livelihood strategies and income generating opportunities: A case study on rural poor households in Kedah, Malaysia - Hassan, Kalthum; Yusof, Rohana; Abdullah, Norehan (Universiti Malaysia Sarawak, 2016)
The objectives of this paper are to uncover the livelihood strategies of the poor households in managing their incomes to sustain the household members' welfare and whether the strategies can be translated as opportunities for poverty alleviation.Adopting qualitative data collection method, an in-depth interview method is used to retrieve information on the expenditure pattern of the households and the underlying reasons for doing so.Five households with various demographic backgrounds are chosen from Mukim Laka Temin, Kubang Pasu District.This study discovers the expenditure of each poor household is managed by a woman and each household has its own unique livelihood strategies which are based on the type of jobs of the household members and the households' spending arrangements.All households prioritize their expenditure, food as the main priority, followed utility bills, transportation, education and others. Most households constantly receive financial supports from various sources such as government agencies and individuals in terms of zakat and donation.The study suggests the livelihoods strategies adopted by the households can be translated into opportunities for the poor households to improve their socio-economic status if the members receive proper provision of trainings and capitals.